Insight on the reduction of copper content in slags produced from the Ausmelt Converting Process - Yuan, Haibin; Cai, Bin; SONG, Xing-cheng; TANG, Du-zuo; Yang, Bin (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The reduction of copper content in converting slag by using process control technology is significant to copper smelter. In this study, the slags produced from the Ausmelt Converting Process for copper matte have been analyzed by X-ray diffraction and chemical analysis. Theoretical calculation and effects of various conditions including lance submerging depth in molten bath, molten bath temperature, the addition of copper matte, and air flow rate were carried out to lower the content in the copper. Theoretical analysis indicates that the decrease of copper content in the slag by reducing Fe3O4, CuFe2O4 and Cu2O in the slag, decreasing the magnetism level of slag and improving the viscosity of slag is feasible at the operating temperature of the molten bath. Experimental results show that the copper content in the slag can be effectively reduced from 22.74 wt. % to 7.70 wt. %. This study would provide a theoretical support and technical guidance for promoting the utilization of mineral resources.